Discovery of a microbial rhodopsin that is the most stable in extreme environments - Jin-gon Shim; Veasna Soum; Kun-Wook Kang; Kimleng Chuon; Shin-Gyu Cho; Ji-Hyun Kim; Seanghun Meas; Alina Pushkarev; Kwanwoo Shin; Kwang-Hwan Jung (iScience, 2021)
Summary: Microbial rhodopsin is a retinal protein that functions as an ion pump, channel, and sensory transducer, as well as a light sensor, as in biosensors and biochips. Tara76 rhodopsin is a typical proton-pumping rhodopsin that exhibits strong stability against extreme pH, detergent, temperature, salt stress, and dehydration stress and even under dual and triple conditions. Tara76 rhodopsin has a thermal stability approximately 20 times higher than that of thermal rhodopsin at 80°C and is even stable at 85°C. Tara76 rhodopsin is also stable at pH 0.02 to 13 and exhibits strong resistance in detergent, including Triton X-100 and SDS. We tested the current flow that electrical current flow across dried proteins on the paper at high temperatures using an electrode device, which was measured stably from 25°C up to 120°C. These properties suggest that this Tara76 rhodopsin is suitable for many applications in the fields of bioengineering and biotechnology.